(3GdCOhjI GdeaQOIs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3cfJ CMJGL Cf CHjf gGgfG eHdZ GdGfJaGY HeYQaI bhi GdCOhjI GdeaQOI ai JQcjH eG jJNP ef GdCOhjI GdeQcHI s
(3BNQgG (B:s
(3JeJ GdebGdI GdMGOjI YTQ ai bhi GdCOhjI GdeaQOI s
(3hgh (B11 (3ebGdI ai bhi GdCOhjI GdeaQOI hCaYGdgG ai GdHOfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B9 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(793/1) s
Keywords: (3GdWHs